'Fake News' and 'Half-truths' in the Framings of Boko Haram Narrative: Implications on International Counterterrorism Responses. Issue 2 (3rd May 2020) - Iwuoha, Victor Chidubem
ABSTRACT: What concerns do official statements, especially government press releases on counterterrorism war against Boko Haram generate for countries outside Nigeria, and what are their counterterrorism responses to such sensitive military information? Nigeria's official counterterrorism and military statements rarely met its intended objectives of improving military's public image, applauding government's counterterrorism efforts, and attracting international counterterrorism support. It, however, depicted government's tendency in the use of 'fake news' and 'half-truths' in blanketing loopholes in its counterterrorism war against Boko Haram. This article argues that government's adoption of 'fake news' and false statements, as 'technology of security governance, ' in the framings of Boko Haram's narrative and counterterrorism analysis is implicated in the shrinkage of international counterterrorism assistance (i.e. troop contribution, intelligence support, military financing, weapons supply, military trainings, cyber-security support, etc.), and consequently the intractability of Boko Haram insurgency. I elicit primary data from top military officers. I conclude by reflecting on a broad counterinsurgency information analysis model that will encompass new techniques for exclusive investigative inquiry in sorting out pieces of false information that are intricately mixed up in true statements.